2019
DOI: 10.1186/s13014-019-1285-1
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric impact of intrafraction motion on boosts on intraprostatic lesions: a simulation based on actual motion data from real time ultrasound tracking

Abstract: Background Intrafraction motion is particularly problematic in case of small target volumes and narrow margins. Here we simulate the dose coverage of intraprostatic lesions (IPL) by simultaneous integrated boosts (SIB). For this purpose, we use a large sample of actual intrafraction motion data. Methods Fifty-three h of intra-fraction motion of the prostate were recorded in real-time by 4D ultrasound (4DUS) during 720 fractions in 28 patients. We simulate spherical IPLs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Ballhausen et al reported a simulation study for the dosimetric impact from intrafraction motion on the DIL boost treatment using EBPT and found that the DILs can be covered by 90% of SIB doses with 2mm margin on them. (36) Advanced IMPT provides much better dosimetry than the EBPT, thanks to the sharp distal falloff from the proton brag peak. However, IMPT is sensitive to range/setup uncertainties and anatomy changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ballhausen et al reported a simulation study for the dosimetric impact from intrafraction motion on the DIL boost treatment using EBPT and found that the DILs can be covered by 90% of SIB doses with 2mm margin on them. (36) Advanced IMPT provides much better dosimetry than the EBPT, thanks to the sharp distal falloff from the proton brag peak. However, IMPT is sensitive to range/setup uncertainties and anatomy changes.…”
Section: Discussionmentioning
confidence: 99%
“…Ballhausen et al reported a simulation study for the dosimetric impact from intrafraction motion on the DIL boost treatment using XRT and found that the DILs can be covered by 90% of SIB doses with 2 mm margin on them. 36 …”
Section: Discussionmentioning
confidence: 99%
“…The data we acquired was used to validate the random walk model of intra-fraction motion 1 , investigate a potential impact of patient couch shifts on intra-fraction motion 2 , to estimate the impact of ultrasound probe pressure on intra-fraction drift of the prostate 3 , to show that a shorter treatment time reduces the severity of intra-fraction motion 4 and to estimate the dosimetric impact of intra-fraction motion on boosts on intra-prostatic lesions 5 .…”
Section: Background and Summarymentioning
confidence: 99%
“…The data we acquired was used to validate the random walk model of intra-fraction motion 1 , investigate a potential impact of patient couch shifts on intra-fraction motion 2 , to estimate the impact of ultrasound probe pressure on intra-fraction drift of the prostate 3 , to show that a shorter treatment time reduces the severity of intra-fraction motion 4 and to estimate the dosimetric impact of intra-fraction motion on boosts on intra-prostatic lesions 5 .…”
Section: Background and Summarymentioning
confidence: 99%